2020
DOI: 10.3846/jbem.2020.11927
|View full text |Cite
|
Sign up to set email alerts
|

Valuation and Underpricing of Turkish Ipos

Abstract: This study utilizes prospectuses and supplementary valuation reports to investigate the relationship between underwriters’ valuation and underpricing in 113 firms going public on Borsa Istanbul. It argues that underwriter discretion in the valuation is crucial to underpricing in the Turkish market, where fixed price is the dominant method of offering and retail investor allocation is large. Building on the overpricing theories, the study hypothesizes and finds that optimistic valuation bias is a significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 49 publications
(124 reference statements)
5
24
0
Order By: Relevance
“…They explain that underwriters deliberately overestimate IPOs to justify applying high levels of discounts. Rasheed et al (2018), Roosenboom (2012) and Tutuncu (2020) find that discounts depend on valuation optimism. Additionally, Cassia et al (2004), Paleari et al (2014) and Vismara et al (2015) find that underwriters perform a biased selection of peers to overestimate IPOs.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 97%
See 3 more Smart Citations
“…They explain that underwriters deliberately overestimate IPOs to justify applying high levels of discounts. Rasheed et al (2018), Roosenboom (2012) and Tutuncu (2020) find that discounts depend on valuation optimism. Additionally, Cassia et al (2004), Paleari et al (2014) and Vismara et al (2015) find that underwriters perform a biased selection of peers to overestimate IPOs.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 97%
“…Actually, only a limited number of studies examining IPOs discounts can be found due to the public unavailability of such information. Most of these studies report that discounts are applied to FVE before setting FOP (Cassia et al, 2004;Deloof et al, 2009;Paleari et al, 2014;Rasheed et al, 2018;Roosenboom, 2012;Tutuncu, 2020;Vismara et al, 2015). They explain that underwriters deliberately overestimate IPOs to justify applying high levels of discounts.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The first day of abnormal positive return (underpricing) within Initial Public Offering (IPO) has been pragmatically proven in every financial market (Mohd-Rashid, Masih, Abdul-Rahim, & Che-Yahaya, 2018;Tutuncu, 2020). The anomaly of initial return is persistent, and this has also been reported in Pakistan, hence considered as a universal phenomenon (Aslam & Ullah, 2017;Khalid & Farhat, 2018;Sohail, Raheman, Zakaria, & Farhat, 2018a).…”
Section: Introductionmentioning
confidence: 99%